Pengembangan Media Augmented Reality Pada Mata Pelajaran IPAS Materi Benda Langit Kelas VI Sekolah Dasar - Lola Palupi; Fahrur Rozi; Robenhart Tamba; Imelda Free Unita Manurung; Suyit Retno (Jurnal Keluarga Sehat Sejahtera, 2026)
The purpose of this study was to determine the validity, practicality, and effectiveness of Augmented Reality-based learning media developed on celestial bodies material for Grade VI students of SDN 106806 Cinta Rakyat. The type of research used was Research and Development (R&D) using the ADDIE model, which consists of 5 stages: Analysis, Design, Development, Implementation, and Evaluation. The validation results by the media expert on the Augmented Reality-based learning media assisted by Assemblr EDU obtained a score with a percentage of 97% with the criteria "Very Feasible". The validation results by the material expert obtained a score with a percentage of 91.67% with the criteria "Very Feasible". The media assessment results by the teacher obtained a score with a percentage of 92% with the criteria "Very Practical". Meanwhile, the student response results obtained a score with a percentage of 94% with the criteria "Very Practical". Based on the implementation results, an improvement in student learning outcomes was found, where the average score on the pre-test was 44.77 while the average score on the post-test was 87.07. Learning using Augmented Reality media assisted by Assemblr EDU in Grade VI on celestial bodies material was proven effective, as evidenced by an average N-Gain score of 0.776 in the "High" category and an N-Gain percentage of 77.60%.